Inhibition of the NLRP3 inflammasome improves lifespan in animal murine model of Hutchinson–Gilford Progeria - Alvaro González‐Dominguez; Raúl Montañez; Beatriz Castejón‐Vega; Jéssica Nuñez‐Vasco; Débora Lendines‐Cordero; Chun Wang; Gabriel Mbalaviele; José M Navarro‐Pando; Elísabet Alcocer‐Gómez; Mario D Cordero (EMBO Molecular Medicine)
Abstract Inflammation is a hallmark of aging and accelerated aging syndromes such as Hutchinson–Gilford progeria syndrome (HGPS). In this study, we present evidence of increased expression of the components of the NLRP3 inflammasome pathway in HGPS skin fibroblasts, an outcome that was associated with morphological changes of the nuclei of the cells. Lymphoblasts from HGPS patients also showed increased basal levels of NLRP3 and caspase 1. Consistent with these results, the expression of caspase 1 and Nlrp3, but not of the other inflammasome receptors was higher in the heart and liver of Zmpste24−/− mice, which phenocopy the human disease. These data were further corroborated in LmnaG609G/G609G mice, another HGPS animal model. We also showed that pharmacological inhibition of the NLRP3 inflammasome by its selective inhibitor, MCC950, improved cellular phenotype, significantly extended the lifespan of progeroid animals, and reduced inflammasome‐dependent inflammation. These findings suggest that inhibition of the NLRP3 inflammasome is a potential therapeutic approach for the treatment of HGPS.